FEATURES OF PRODUCTIVITY, RIPENING AND GERMINATION OF JUNIPER SEEDS - Yuldashov Yakubjon Khatamovich; Ubaydullaev Farkhod Bakhtiyarullaevich; Khatamov Bakhramjon Yakubjanovich (American Journals, 2023)
The article presents the results of a study on the Features of fruiting, ripening and germination of juniper seeds. The time of flowering, ripening of pine berries was determined, the summary data on the quality of pine berries and seeds of forest-forming juniper species, the time of biological dormancy, how to avoid biological dormancy and obtain the results of sowing in a short time were studied. The development of seedlings in natural conditions, the difference between juniper seedlings of various species from each other has been studied.
Keywords: juniper turkestanica, juniper semiglobosa, juniper seravschanica, seed;seeds, seedlings, pine berries, vegetation, slopes and expositions